Intestinal α-glucosidase and some pancreatic enzymes inhibitory effect of hydroalcholic extract of Moringa stenopetala leaves - Toma, Alemayehu (BioMed Central, 2014)
BACKGROUND: Moringa stenopetala has been used in traditional health systems to treat diabetes mellitus. One of the successful methods to prevent of the onset of diabetes is to control postprandial hyperglycemia by the inhibition of α-glucosidase and pancreatic α-amylase activities, resulting in the aggressive delay of the carbohydrate digestion of absorbable monosaccharides. The aim of the present study is to investigate the effect of the extract of the leaves of Moringa stenopetala on α-glucosidase, pancreatic α-amylase, pancreatic lipase, and pancreatic cholesterol esterase activities, and, therefore find out the relevance of the plant in controlling blood sugar and lipid levels. METHODS: The dried leaves of Moringa stenopetala were extracted with hydroalcoholic solvent and dried using rotary vapor under reduced pressure. The dried extracts were determined for the total phenolic compounds, flavonoid content and condensed tannins content by using Folin-Ciocateu’s reagent, AlCl(3) and vanillin assay, respectively. The dried extract of plant-based food was further quantified with respect to intestinal α-glucosidase (maltase and sucrase) inhibition and pancreatic α-amylase inhibition by glucose oxidase method and dinitrosalicylic (DNS) reagent, respectively. RESULTS: The phytochemical analysis indicated that flavonoid, total phenolic, and condensed tannin contents in the extract were 71.73 ± 2.48 mg quercetin equivalent/g of crude extract, 79.81 ± 2.85 mg of gallic acid equivalent/g of crude extract, 8.82 ± 0.77 mg catechin equivalent/g of crude extract, respectively. The extract inhibited intestinal sucrase more than intestinal maltase with IC(50) value of 1.47 ± 0.19 mg/ml. It also slightly inhibited pancreatic α-amylase, pancreatic lipase and pancreatic cholesterol esterase. CONCLUSION: The result demonstrated the beneficial biochemical effects of Moringa stenopetala by inhibiting intestinal α-glucosidase, pancreatic cholesterol esterase and pancreatic lipase activities. A daily supplement intake of the leaves of Moringa stenopetala may help in reducing hyperglycemia and hyperlipidemia.